Corporate Social Responsibility in Malaysian Apparel Manufacturing Industry: A Study on Corporate Social Responsibility Website Reporting - Ramakrishnan, Suresh; Hishan, Sanil S.; Kanjanapathy, Malini (International Review of Management and Marketing, 2016)
ABSTRACT: A well planned and implemented Corporate Social Responsibility (CSR) programs could give any company a competitive advantage over its competitors. However, the way it is communicated to its stakeholders will be one of the deciding factors. This study examines how the WRAP certified apparel manufacturers in Malaysia communicate their CSR programs on their company website. This study identifies the dimensions of CSR they focus while they communicate their CSR initiatives to their stakeholders and how companies use their company website to communicate their CSR related activities. The study employed the content analysis technique and descriptive statistics using percentages to analyse the company websites. The companies CSR activities were divided into 5 dimensions namely employee relations, product quality, community relations, environmental issues and diversity issues. Findings suggest that the Malaysian apparel companies understand the importance of CSR and consider it as one of the factors which can give the companies an edge over their competitors. However the companies can still improve in their communication by using more pictures and giving some specifics about the product quality and diversity dimension. Furthermore, the remaining 40% of the companies have to understand the importance of CSR and communicate their CSR related activities on their company website. Keywords: Corporate Social Responsibility, Communication, Apparel Industry, Malaysia JEL Classifications: M000, M10, M14